Sea monster's first day ebook - Messner, Kate (2023)
E. B. White Award–winning author: “Ample aquatic puns and boisterous, mixed-media artwork . . . A splashy story about fitting in.” — Publishers Weekly   Sea monster Ernest is starting his first day of school. But starting school is a big job! Fitting in when you’re a sea monster is tough enough, and there’s so much to learn and do—reading, singing, playing hide-and-seek with the fishermen, lunchtime in the algae patch . . .   This funny, charming twist on the worries and joys of starting school will reassure and delight the smallest children and the largest sea monsters alike.   “Genuine enthusiasm and humor.” — School Library Journal